2017
DOI: 10.1523/jneurosci.3525-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Subcortical Amygdala Route for Faces Irrespective of Spatial Frequency and Emotion

Abstract: There is significant controversy over the existence and function of a direct subcortical visual pathway to the amygdala. It is thought that this pathway rapidly transmits low spatial frequency information to the amygdala independently of the cortex, and yet the directionality of this function has never been determined. We used magnetoencephalography to measure neural activity while human participants discriminated the gender of neutral and fearful faces filtered for low or high spatial frequencies. We applied … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 78 publications
8
97
1
Order By: Relevance
“…Convincingly, the results showed that amygdala activity arose for BSF and LSF faces, but not for HSF stimuli, arguing in favour of a subcortical pathway biased towards low spatial frequencies (Vuilleumier et al, 2003). Since this report, a number of other studies have highlighted the importance of LSF in emotional face processing (e.g., Bocanegra & Zeelenberg, 2009;Mermillod, Vuilleumier, Peyrin, Alleysson, & Marendaz, 2009), yet the reliance of the subcortical pathway on LSF remains disputed (e.g., De Cesarei & Codispoti, 2013;Garrido, 2012;Garvert, Friston, Dolan, & Garrido, 2014;McFadyen, Mermillod, Mattingley, Halasz, & Garrido, 2017).…”
Section: Introductionmentioning
confidence: 61%
“…Convincingly, the results showed that amygdala activity arose for BSF and LSF faces, but not for HSF stimuli, arguing in favour of a subcortical pathway biased towards low spatial frequencies (Vuilleumier et al, 2003). Since this report, a number of other studies have highlighted the importance of LSF in emotional face processing (e.g., Bocanegra & Zeelenberg, 2009;Mermillod, Vuilleumier, Peyrin, Alleysson, & Marendaz, 2009), yet the reliance of the subcortical pathway on LSF remains disputed (e.g., De Cesarei & Codispoti, 2013;Garrido, 2012;Garvert, Friston, Dolan, & Garrido, 2014;McFadyen, Mermillod, Mattingley, Halasz, & Garrido, 2017).…”
Section: Introductionmentioning
confidence: 61%
“…For example, prior work has shown that PCA components underlying the LPP are differentially sensitive to intrinsic or extrinsic experimental effects, with extrinsic effects modulating later PCA components in particular (MacNamara et al, 2009). Here, an early, occipital PCA component peaking around 500 ms post-stimulus onset was found to be correlated with BOLD activation in the amygdala, perhaps reflecting the amygdala’s role in the rapid identification and early processing of threatening stimuli (e.g., McFadyen, Mermillod, Mattingley, Halász, & Garrido, 2017). Using mean area amplitudes (which extended until stimulus offset), the LPP was correlated with activation in the insula - a brain region implicated in the conscious awareness and anticipation of threat (Critchley, Mathias, & Dolan, 2002; Phelps et al, 2001).…”
Section: Discussionmentioning
confidence: 81%
“…However, there is some debate on how such rapid perception is accomplished. A fast subcortical thalamus‐amygdala route bypassing the visual cortex is thought to transmit coarse face‐related information (LeDoux, 2009; Morris et al, 1998), but its role in face perception is controversial (Krolak‐Salmon et al, 2004; Pessoa & Adolphs, 2011), including whether it is fear‐specific (Méndez‐Bértolo et al, 2016) or non‐specific to expression (Garvert, Friston, Dolan, & Garrido, 2014; McFadyen et al, 2017). On the other hand, multiple fast cortical pathways forming part of a feedforward and feedback mechanism consistute an equally plausible mechanism for rapid expression perception (Liu & Ioannides, 2010; Pessoa & Adolphs, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is some debate on how such rapid perception is accomplished. A fast subcortical thalamus-amygdala route bypassing the visual cortex is thought to transmit coarse face-related information (LeDoux, 2009;Morris et al, 1998), but its role in face perception is controversial (Krolak-Salmon et al, 2004;Pessoa & Adolphs, 2011), including whether it is fear-specific (M endez-B ertolo et al, 2016) or non-specific to expression (Garvert, Friston, Dolan, & Garrido, 2014;McFadyen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%